1989
DOI: 10.1085/jgp.94.5.813
|View full text |Cite
|
Sign up to set email alerts
|

Veratridine modification of the purified sodium channel alpha-polypeptide from eel electroplax.

Abstract: In the interest of continuing structure-function studies, highly purified sodium channel preparations from the eel electroplax were incorporated into planar lipid bilayers in the presence of veratridine. This lipoglycoprotein originates from muscle-derived tissue and consists of a single polypeptide. In this study it is shown to have properties analogous to sodium channels from another muscle tissue (Garber, S. S., and C. Miller. 1987. J0urna/ of General Physiology. 89:459-480), which have an additional protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 30 publications
(66 reference statements)
4
25
1
Order By: Relevance
“…Na ÷ channels incorporated into lipid bilayers with the aid of veratridine show clear voltage-dependent block by TTX with Kd increasing with depolarization. This has been reported for electroplax channels (Duch et al 1989) as well as those from lobster walking leg nerves. In both preparations batrachotoxin-modified channels are also blocked in a potential-dependent fashion (Levinson et al 1986;Castillo et al 1992).…”
Section: Block By Guanidinium Toxinssupporting
confidence: 64%
See 2 more Smart Citations
“…Na ÷ channels incorporated into lipid bilayers with the aid of veratridine show clear voltage-dependent block by TTX with Kd increasing with depolarization. This has been reported for electroplax channels (Duch et al 1989) as well as those from lobster walking leg nerves. In both preparations batrachotoxin-modified channels are also blocked in a potential-dependent fashion (Levinson et al 1986;Castillo et al 1992).…”
Section: Block By Guanidinium Toxinssupporting
confidence: 64%
“…Thus in the rare case of one-channel patches the potential at which fo=0.5 varied by 30 mV. In other cases the results are complicated since depolarization also increases the number of conducting channels (Duch et al 1989). Membranes with single lobster nerve channels show closures on the order of milliseconds (fast process), seconds (slow process), and minutes, leading to fast and slow types of fo that increased with depolarization and have different midpoint potentials of -122 and -95 mV, respectively.…”
Section: Artificial Membranesmentioning
confidence: 98%
See 1 more Smart Citation
“…Vr values were interpolated using the data from +30 to -30 mV and given with respect to the chamber containing only NaCI (extracellular aspect of the channel). electroplax (KI/2 = 17.5 nM; a = 0.53; Duch et al, 1989) and the TIX K1/2 for sodium channels from lobster leg nerves determined with flux studies (12 nM; Barnola and Villegas, 1976).…”
Section: Ttx Blockmentioning
confidence: 99%
“…Gordon et al (1987) demonstrated that this rat brain Na channel preparation contained 18% R I Na channel and some mixture of Rn and Rin Na channels by immunological criteria (the antibodies used to distinguish R n Na channels would be expected to crossreact with RHI since the antigen had 75% homology between these two types). Although there have been other reports in the literature of low conductance BTX-and VER-activated channels from brain Green et al, 1987;Duch et al, 1988Duch et al, , 1989, it has not been clear whether these low conductance states are due to multiple substates, of a single channel or multiple channel types.…”
Section: Comparison Of Type a And Type B Channels With Previously Desmentioning
confidence: 99%